Problems of developing a unified concept of the right of access to the information and its contents - Капінус, Людмила Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The analysis of the content of the notion «right on the access to information» and its correlation withrelated rights is done. The author’s definition of «information» is formulated and the content of the right onaccess to information is defined. The certain steps towards improvements of the national informationallegislation in this sphere are offered.